Contribution of Agricultural Sector Towards Regional Income Inequality of Sumatera Economic Corridor - Dany Juhandi; Irham Irham; Jamhari Jamhari (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2016)
Finding of previous studies shows that Sumatera Economic Corridor is categorized as the highest income inequality. The Indonesian goverment enacts MP3EI (Master Plan for the Acceleration and Expansion of Indonesia Economic Development) program to promote equitable development where each economic corridor owns strategic economic sector. The objective of this study is to analyze the contribution of agricultural sector on income inequality in Sumatera Economic Corridor (SEC) using a weighted coefficient of variation. We use secondary time series data of Gross Regional Domestic Product (GRDP), number of population, and per capita income of a time range between 2002 and 2013. Data analysis shows that agricultural sector has the least contribution on income inequality. Consequently, goverment policy should be focusing on the development of agricultural sector in Sumatera Economic Corridor